STUDI PENGETAHUAN, DIET, AKTIFITAS FISIK, MINUM OBAT DAN KADAR GLUKOSA DARAH PASIEN DIABETES MELITUS TIPE 2 SEBELUM DAN SETELAH PENDAMPINGAN GIZI DI PUSKESMAS RIJALI KOTA AMBON TAHUN 2012 - Khartini Kaluku; Nurhaedar Jafar; Citrakesumasari Citrakesumasari (Poltekkes Kemenkes Maluku, 2017)
Diabetes mellitus has become the world's health problems. The prevalence and incidence of these diseases has increased drastically in the newly industrialized countries and developing countries, including Indonesia's. This research is an experimental research by approach nonrandomized one group pre and posttest design which is to see the difference knowledge, diet, physical activity, medication and the patient's blood glucose levels diabetes mellitus before and after accompaniment nutrition in Puskesmas Rijali Ambon. The population of this research is all patients diabetes mellitus, sampling is done by using the technique of purposive sampling with the total sample as many as 26 people. The result showed that after the accompaniment of nutrition increase knowledge 42,3%, compliance intake of energy 23,1%, compliance intake of proteins 23.1%, compliance fat intake 38.5%, compliance intake of carbohydrates 3.9%, compliance physical activity 30,8%, compliance medication 30,8% and blood glucose levels are 42,3%. Attesting four main pillars handling DM use the model of nutritional accompaniment give a flanking control blood sugar of 70%. Of the results obtained, can be concluded that the educational model counselling of nutrition is very influential to increase knowledge and compliance respondents against the diet, physical activity, medication and blood glucose levels. Keywords: Blood glucose levels, diet, knowledge, diet, medication, physical activity